Emotional intelligence in incarcerated men with psychopathic traits. - Ermer, Elsa; Kahn, Rachel E; Salovey, Peter; Kiehl, Kent A (Journal of personality and social psychology, 2012)
The expression, recognition, and communication of emotional states are ubiquitous features of the human social world. Emotional intelligence (EI) is defined as the ability to perceive, manage, and reason about emotions, in oneself and others. Individuals with psychopathy have numerous difficulties in social interaction and show impairment on some emotional tasks. Here, the authors investigate the relation between EI and psychopathy in a sample of incarcerated men (N = 374), using the Psychopathy Checklist-Revised (PCL-R; Hare, 2003) and the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT; Mayer, Salovey, & Caruso, 2002). The MSCEIT is a well-validated ability-based EI measure that does not rely on self-report judgments of emotional skills. The Hare PCL-R is the gold standard for the assessment of psychopathy in clinical populations. Controlling for general intelligence, psychopathy was associated with lower EI. These findings suggest individuals with psychopathy are impaired on a range of EI abilities and that EI is an important area for understanding deficits in psychopathy.
Keywords: Adolescent; Adult; Emotional Intelligence; Humans; Male; Mental Disorders; Middle Aged; Prisoners; Questionnaires; Young Adult